Rancang Bangun Sistem Pengukuran Kinerja Baterai pada Baggage Towing Tractor berbasis NodeMCU ESP8266 Aplikasi Android - I Gede Made Putra Suardana; Ida Bagus Made Harisanjaya Adi Nugraha; Dewa Gede Agung Padmanaba Pemayun; Ida Bagus Irawan Purnama; I Gede Ketut Sri Budarsa; Ida Bagus Ketut Sugirianta; Anak Agung Ngurah Gde Sapteka (LPPM STT Terpadu Nurul Fikri, 2022)
An electric vehicle uses increasing in Indonesia. Airport services are also advancing the development of electric cars on Baggage Towing Tractors (BTT). BTT is used to attract aircraft baggage to the terminal baggage queue. BTT uses an electric engine as a driving force and an 80V battery as a voltage source. If the BTT battery is not managed correctly, then it is an effect on the battery life. This battery is prone to over-voltage, under-voltage, and over-heat. The project is necessary to develop a system that makes it easier for users to monitor battery performance and technicians during maintenance. The concept of this system is based on an android application. This application will provide real-time information about battery voltage, temperature, and humidity through Firebase Database. The data received by sensors is sent to the database via a microcontroller, which is connected to a Wi-Fi network. The android application will access the database and display data in real-time by ignoring previous data. This system is designed for users to determine the condition of the BTT battery that will be used. The system was tested to evaluate measurement accuracy and speed of updating data. From the test result, the level of accuracy system is around 97%, and it’s rated as working optimally.